Pathogenic potential of environmental resident fungi from ornithogenic soils of Antarctica. Issue 12 (December 2017) - de Sousa, Jordana R.P.; Gonçalves, Vívian N.; de Holanda, Rodrigo A.; Santos, Daniel A.; Bueloni, Cinthia F.L.G.; Costa, Adriana O.; Petry, Maria V.; Rosa, Carlos A.; Rosa, Luiz H.
Abstract: We assessed the diversity of cultivable fungi in the ornithogenic soil nests of bird species like Phalacrocorax atriceps, Macronectes giganteus, Pygoscelis antarcticus, and Pygoscelis papua in the Antarctic islands. From 481 fungi isolated at 15 °C, only 50 displayed growth at 37 °C, and were identified as 14 species of 15 genera. Aspergillus fumigatus, Penicillium chrysogenum, and Rhodotorula mucilaginosa were the most abundant species obtained. Fifty taxa grew at 40 °C; displayed haemolytic and phospholipase activities; produced tiny spores, capsule, and melanin; showed growth at different pH; and showed resistance to amphotericin B. Interestingly, the minimum inhibitory concentration of amphotericin B increased by 5–10 fold for some A. fumigatus isolates after phagocytosis by amoeba. Our results show relations among fungal community compositions present in Antarctic ornithogenic soil and their pathogenic risk to humans in vitro . As the Antarctica Peninsula is a major region of the planet affected by global climate changes, our results, though preliminary, raise concerns about the dispersal of potential pathogenic microbes present in Antarctic substrates by wild birds, which can fly great distances and spread potential pathogens mainly to South America and Oceania. Graphical abstract: Highlights: Fungal isolates showed virulence factors in vitro . Fungal Antarctic isolates can represent potential pathogenic risk to humans. Ornithogenic soils can be a reservoir of fungi with pathogenic potential. Some fungi present in Antarctica present a potential pathogenic risk to humans.